2018
DOI: 10.1016/j.erss.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

System building in the Kenyan electrification regime: The case of private solar mini-grid development

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…The trajectory of village-sized mini grids started in the turn of the millennium in some countries of West Africa (Senegal, Burkina Faso, and Mali) and also Morocco, with more than 200 systems by 2018 [29]. While the first mini grids were financed with donors and international support, lately, a strong inclusion of private companies focusing on the business of mini grids for rural electrification has been seen.…”
Section: Mini Grid Deployment and Tendersmentioning
confidence: 99%
“…The trajectory of village-sized mini grids started in the turn of the millennium in some countries of West Africa (Senegal, Burkina Faso, and Mali) and also Morocco, with more than 200 systems by 2018 [29]. While the first mini grids were financed with donors and international support, lately, a strong inclusion of private companies focusing on the business of mini grids for rural electrification has been seen.…”
Section: Mini Grid Deployment and Tendersmentioning
confidence: 99%
“…The latter casts analytical attention on the ways technology and innovation co-evolve with social practices and broader social institutions, creating dominant socio-technical regimes and path dependency that new niches of sustainable technology struggle to compete with and influence in new, sustainable directions. Importantly, as several authors have now shown in relation to energy access (e.g., [8,16,[39][40][41][42]), these socio-technical regimes can look different in remote areas of low-income countries to those studied in the Global North; the latter being the empirical context within which the majority of the socio-technical transitions literature has emerged to date (as analysed, for example, in a recent special issue, see [43,44]). Nevertheless, as demonstrated by the aforementioned recent contributions, these low-income contexts are still subject to similar dynamics, where everyday practices and powerful economic and political interests align with dominant socio-technical regimes (e.g., in the supply of kerosene for cooking and lighting), or with potentially unsustainable alternatives (e.g., expanding grid-connected, coal-fired electricity supply), implying continued utility for socio-technical transitions perspectives within low-income contexts.…”
Section: National Contexts For Fostering Innovation Including Technomentioning
confidence: 99%
“…While purely private models, in which private mini-grid developers rely on private equity and commercial loans to electrify rural villages, exist these models face various policy barriers to upscaling. Although the Kenyan electricity market has been liberalized and opened up to private sector involvement (Kapika & Eberhard, 2013), the current regulatory and policy frameworks are not conducive to private mini-grid development (Pedersen & Nygaard, 2018). Lack of clear policies on options for grid-integration in cases where the national grid arrives at a privately operated site, as well as a national uniform tariff level, are some of the main barriers facing private mini-grid developers.…”
Section: Policy Reflectionsmentioning
confidence: 99%